2021
DOI: 10.1007/s40843-020-1601-9
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional two-dimensional glassy graphene devices for vis-NIR photodetection and volatile organic compound sensing

Abstract: Multifunctional devices are of great interest for integration and miniaturization on the same platform, but simple addition of functionalities would lead to excessively large devices. Here, the photodetection and chemical sensing device is developed based on two-dimensional (2D) glassygraphene that meets similar property requirements for the two functionalities. An appropriate bandgap arising from the distorted lattice structure enables glassy graphene to exhibit comparable or even improved photodetection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Photodetectors play an important role in a wide range of applications, such as optical communication, image sensing, environmental monitoring, biological detection, etc. [1][2][3][4] Material quality and optical properties of the active region of a photodetector directly determine device performance. [5][6][7] To date, commercial photodetectors mainly rely on group IV, III-V, and II-VI semiconductors, which involve complex manufacturing processes under strictly controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Photodetectors play an important role in a wide range of applications, such as optical communication, image sensing, environmental monitoring, biological detection, etc. [1][2][3][4] Material quality and optical properties of the active region of a photodetector directly determine device performance. [5][6][7] To date, commercial photodetectors mainly rely on group IV, III-V, and II-VI semiconductors, which involve complex manufacturing processes under strictly controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…developed a multifunctional FET sensor with channels made of glossy graphene, enabling photodetection (responsivity = 0.22 A W 1– ) as well as chemical liquid sensing (response time < 5 s) at the same time. The glossy graphene has distorted lattice-induced Stone–Wales defects with twisted C–C bonds by 90°, which are advantageous for photodetection and chemical sensing. , Photodetection was achieved by interaction between ambient molecules and the Stone–Wales defects of the glossy graphene. Also, these defects provided abundant adsorption sites that were sensitive to chemical analytes (e.g., acetone and methanol).…”
Section: Prototypical Designmentioning
confidence: 99%
“…Furthermore, this work allows easy incorporation of different functional components such as communication and power modules by the innovative assembly and adhesive strategy, showing its great promise for future in vivo exploration. Similarly, Li et al 356 developed a multifunctional FET sensor with channels made of glossy graphene, enabling photodetection (responsivity = 0.22 A W 1− ) as well as chemical liquid sensing (response time < 5 s) at the same time. The glossy graphene has distorted lattice-induced Stone−Wales defects with twisted C−C bonds by 90°, which are advantageous for photodetection and chemical sensing.…”
Section: Prototypical Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, two-dimensional (2D) materials have been widely fabricated to optically modulate artificial synapses due to their excellent photoresponse, well-developed synthesis methodology and potential integration with complementary metal oxide semiconductor (CMOS) technologies [14,[20][21][22][23][24][25][26][27]. For example, Mennel et al [21] have reported a neural network image-senor array [28] based on WSe 2 for ultrafast image recognition and encoding.…”
Section: Introductionmentioning
confidence: 99%